2022
DOI: 10.1002/adom.202202366
|View full text |Cite
|
Sign up to set email alerts
|

Mn5+ Lifetime‐Based Thermal Imaging in the Optical Transparency Windows Through Skin‐Mimicking Tissue Phantom

Abstract: conditions. We specifically demonstrated that 2D temperature maps of a thermal gradient can be obtained through tissue phantoms mimicking the optical properties of the skin using Ba 3 (VO 4 ) 2 :1% Mn 5+ , 0.5% Er 3+ nanophosphors as luminescent probes and a custom-made setup for lifetime-based luminescence thermometry.These results show the way for the development of ever more efficient luminescent nanothermometers based on doped luminescent centers (i.e., metal ions) that are bright and feature long, tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…To probe the LSPR heating effect, temperature transient curves were investigated by luminescence thermometry using temperature-sensitive NaYF 4 :Lu/Yb/Er upconverting nanoparticles (UCNPs) coexisting with AuNRs. Luminescence thermometry is a versatile and cost-effective remote sensing technique that uses a temperature-dependent optical signal to measure the local temperature around a light-emitting material. , The technique has become extremely popular over the past decade, as it is effective in remotely measuring temperature in micro- and nanostructured systems. , However, the technique has not been explored to probe the LSPR heating effect in the dissociation of amyloid-β fibrils. Here, a second 980 nm beam laser was added to the setup for the excitation of UCNPs, together with a spectrometer to measure the photoluminescence spectrum (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To probe the LSPR heating effect, temperature transient curves were investigated by luminescence thermometry using temperature-sensitive NaYF 4 :Lu/Yb/Er upconverting nanoparticles (UCNPs) coexisting with AuNRs. Luminescence thermometry is a versatile and cost-effective remote sensing technique that uses a temperature-dependent optical signal to measure the local temperature around a light-emitting material. , The technique has become extremely popular over the past decade, as it is effective in remotely measuring temperature in micro- and nanostructured systems. , However, the technique has not been explored to probe the LSPR heating effect in the dissociation of amyloid-β fibrils. Here, a second 980 nm beam laser was added to the setup for the excitation of UCNPs, together with a spectrometer to measure the photoluminescence spectrum (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Luminescence thermometry is a versatile and cost-effective remote sensing technique that uses a temperature-dependent optical signal to measure the local temperature around a light-emitting material. 49,50 The technique has become extremely popular over the past decade, as it is effective in remotely measuring temperature in micro-and nanostructured systems. 51,52 However, the technique has not been explored to probe the LSPR heating effect in the dissociation of amyloid-β fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) studies of Ba 3 (VO 4 ) 2 :0.1% Mn 5+ co-doped with Nd 3+ ions are also in agreement with previous studies for materials singly doped with Mn 5+ ions. 25 It can be concluded that the particles are well crystallized with a tendency to agglomerate (Fig. 1(c)–(f) and Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Furthermore, the spectra show two broad overlapped bands with maxima at 340 nm and ∼305 nm that come from the charge transfer from the (VO 4 ) 3− group. 25,30 The band centered at 340 nm decreases markedly compared to the band at ∼305 nm as the concentration of Mn 5+ increases, while the maximum of the second band gradually shifts from 312 nm to 301 nm for the phosphor doped with 0.1% and 5% of Mn 5+ ions. This may be related to the gradual decrease in the strength of the crystal field that interacts with the (VO 4 ) 3− group resulting from the substitution of larger Ba 2+ ions with smaller Nd 3+ ions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation